LITERASI MATEMATIKA SISWA SMP MELALUI MODEL PROBLEM BASED LEARNING - Asmara, Adi; Risnanosanti, Risnanosanti (Universitas Muhammadiyah Bengkulu, 2019)
Indonesian students' mathematical literacy based on PISA and PIRLS assessments is still in the low category. Mathematical literacy covers how students are able to know and use basic mathematics to solve problems in real life contexts. Problem Based Learning Model is a learning model that can solve problems in real life contexts by facilitating the development of junior high school students' mathematical literacy. The main principle of Problem Based Learning emphasizes mathematical problems that are human activities and must be meaningful for students, become a motivator to improve mathematical literacy skills through the stages of learning. This article examines the mathematical literacy ability of SMP Negeri 11 Bengkulu students before and after going through the Problem Based Learning Model. Students' mathematical literacy skills prior to the application of the Problem Based Learning model have a percentage of 25% for the medium category and 75% are in the low category. Then for students' mathematical literacy ability after applying the Problem Based Learning model has a percentage of 5% for the medium category, 90% is in the low category, and 5% is in the high category. The results of inferential statistical analysis (Paired Sample T-test) obtained a significance value 0.05. This means that there is an increase in students' mathematical literacy skills after the application of the Problem Based Learning model in class VII SMP Negeri 11 Bengkulu City.Keywords: Literacy Ability, Problem Based Learning